PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 46 CAKRANEGARA - Haeni, Yuli; Nurhasanah; Alimuddin, Nurkhaerat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of Pancasila Education of fifth-grade students at SDN 46 Cakranegara, this is caused by the implementation of learning models that do not actively involve students, learning that is not student-centered, and the use of learning media that is less interactive. The purpose of this study is to determine the effect of the Teams Games Tournament learning model on the learning outcomes of fifth-grade students in Pancasila Education. This study uses a quantitative research method of the Quasi-Experimental type with a Non-Equivalent Control Group design. The sample in this study was class VA as the experimental class and class VB as the control class determined through saturated sampling techniques. Data were collected through test instruments and observations, then analyzed using the Independent Sample t-Test. The results of this study indicate that the t-count (-3.175) > t-table (2.014) with an Effect Size of 0.93. Therefore, the Teams Games Tournament learning model has a positive and effective influence in improving the learning outcomes of Pancasila Education of fifth-grade students at SDN 46 Cakranegara.